Methodological Fundamentals of the Art of Music (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, the history of the development of musical art and its theoretical and methodological foundations are discussed, as well as the processes of forming the psychological effects of modern music on the minds of young people. Musical approaches to the history of the development of aleatoric flow music and sonorica techniques, modern music and art, and its theoretical foundations will be discussed.